The utility of BDI-II in assessment of pre- and postpartum depression symptoms and their relation to labor pain - Čuržik, Doris (Array, 2012)
Background: It’s argued that the total Beck Depression Inventory II (BDI-II) score likely overestimates depression in pregnant women given the overlap between depressive and somatic symptoms during pregnancy. The aim of this study was to explore the structure and the intensity of depression symptoms during pregnancy and two months postpartum. In populations with high incidence of somatic complaints (i.e. chronic pain sufferers) depression is also often related to higher pain intensity. Therefore, the relationships between depression symptoms and expected, perceived and recalled labor pain were also examined. Subjects and methods: 60 healthy primiparas enrolled the study. BDI-II as measure of depression was completed during the late stage of pregnancy and two months postpartum. Assessments of maximum and average labor pain were completed in three different time periods (before – expected labor pain, during/immediately after labor – perceived labor pain, and one month postpartum – recalled labor pain). Results: Depression symptoms measured two months postpartum were significantly lower than the ones measured during the late stage of pregnancy (t=8.377, df=49, p<.01). During the late stage of pregnancy, BDI-II items with highest mean scores were those measuring somatic symptoms of depression. Depression measured during the late stage of pregnancy correlated significantly with maximum labor pain expectancies (r = .41, p< .01). Conclusion: The use of standardized questionnaires with a high rate of somatic items such as BDI-II may not be the best solution when screening for mood disorders in pregnant women. Levels of depression share a significant relationship with maximum labor pain expectancies only.